Enhanced DC conductivity of low volume-fraction nano-particulate suspensions in silicone and perfluorinated oils. - Wilson, Stephen A.; Libor, Zsuzsanna; Skordos, Alexandros A.; Zhang, Qi (IOP Publishing, 2009)
The contrasting DC conductivities of several different types of nanoparticles (nickel, barium titanate and magnetite) suspended in both silicone and perfluorinated oils have been measured and compared. Enhanced DC conductivity through interaction between the particles and the fluid has been demonstrated even at quite moderate fields and different types of nanoparticles have been shown to exhibit different behavioural trends. Whilst the DC enhancement is partly related to the concentration (or spatial arrangement) of the particles as expected, there is clear evidence that energy-activated (electric-field activated) processes also play a major role. It can be said that effective medium theories based solely on the electrical properties and volume fractions of the component materials have limited applicability when assessing the DC conductivity of these nanoparticle-fluid combinations at low volume fractions.